Dakwah Muslim Progresif Dalam Menyikapi Kesetaraan Gender - Assya'bani, Ridhatullah; Falach, Ghulam (IAIN Samarinda, 2020)
Women has long been in a relatively less beneficial position in society compared to their male couterparts. In the Muslim world, this situation has also long been a source of serious discussions among ulamas (experts), especially since Islam is founded upon the spirit of equality and anti-oppression. This paper, thus, deals with ideas from the camp of Progressive Muslims regarding gender equality, especially on the implementation of Islamic Da’wa (proselytizing) to promote gender equality according the perspective of Progressive Muslim. Utilizing literary approach, this paper argues that the implementation of the Da’wa of Progressive Muslims stresses on several aspects such as the importance of critical thinking, being no too textual, being moderate, not being apologetic, and being open about gender issues.Keywords: Da’wa, gender equality, progressive Muslims, and Omid Safi.